The Impact of the Absence of Mental Health Education on Student Teachers’ Well-Being: A Survey Study - Madiha Ghori; Sari Hidayati (AT-TA'LIM, 2026)
This study aimed to explore and analyse the impact of the absence of mental health education in teacher training programs on student teachers' well-being. A survey research design was utilised to conduct the study. The findings reveal that the lack of structured mental health education in pre-service teacher training has significant consequences for student teachers' mental well-being. It leaves them feeling underprepared to manage stress, burnout, and the emotional demands of the teaching profession. The study highlights the need for systemic changes in teacher education, advocating for the inclusion of mental health literacy in training programs to enhance resilience, reduce burnout, and improve student teachers’ well-being and future effectiveness in the classroom.